2022
DOI: 10.1057/s41599-022-01289-z
|View full text |Cite
|
Sign up to set email alerts
|

Organizational culture as a mediator of credible leadership influence on work engagement: empirical studies in private hospitals in East Java, Indonesia

Abstract: The success of health services in hospitals depends on the work engagement of medical and non-medical personnel in providing quality services for patients. Engaged employees will be more proactive, take the initiative to collaborate with others, and are committed to achieving high-quality performance. A leader’s ability in an organization is a major factor in building a work ethic in the organization, instilling values, norms, and ethics through organizational culture into employee work behavior, such as work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 41 publications
1
19
0
2
Order By: Relevance
“…Previous studies have revealed that culture is important to improve the development of organizations and, in turn, to improve workers' QWL in hospitals. As an example, a study from two private hospitals in the city of Madiun, Indonesia, testified that a positive organizational culture helped 10.3389/fpsyg.2023.1139341 Frontiers in Psychology 04 frontiersin.org medical physicians feel satisfied with the work environment and boosted their active work engagement (Srimulyani and Hermanto, 2022). A national survey in America during the pandemic proved that organizational culture had an effect on work expectations and achievement motivation among physicians (Young et al, 2020).…”
Section: The Moderating Role Of Organizational Culturementioning
confidence: 99%
“…Previous studies have revealed that culture is important to improve the development of organizations and, in turn, to improve workers' QWL in hospitals. As an example, a study from two private hospitals in the city of Madiun, Indonesia, testified that a positive organizational culture helped 10.3389/fpsyg.2023.1139341 Frontiers in Psychology 04 frontiersin.org medical physicians feel satisfied with the work environment and boosted their active work engagement (Srimulyani and Hermanto, 2022). A national survey in America during the pandemic proved that organizational culture had an effect on work expectations and achievement motivation among physicians (Young et al, 2020).…”
Section: The Moderating Role Of Organizational Culturementioning
confidence: 99%
“…According to Kahn, WREN is "a person's self-connection with his or her job or work by integrating physical, cognitive and emotional resources". While the positive outcomes of engaged employees have been recognised in the previous literature [71,72], the literature also indicates the adverse consequences for an organisation associated with disengaged employees [73]. Past literature suggests that engaged employees are less likely to face the risk of BOT [74,75].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Untuk beberapa kasus, WFH telah diadopsi cukup lama. Bahkan sejumlah sarjana menyimpulkan bahwa WFH telah menjadi bagian dari budaya kerja di birokrasi pemerintahan (Al Shehri et al, 2017;Srimulyani & Hermanto, 2022). Praktek ini untuk beberapa kondisi telah berhasil meningkatkan kinerja organisasi publik, meningkatkan layanan, serta membuat organisasi publik lebih efektif dan efisien (Napitu et al, 2021).…”
Section: Pendahuluanunclassified